Impact of Fast-Food Consumption on Overweight Among Young Adults in Sri Lanka - Hunuwala Malawarage Priyanath; P.A.N.C. Dasanayaka (International Journal of Education, Teaching, and Social Sciences, 2022)
The study aims to find out how fast-food consumption affects the overweight problem among young adults. A cross-sectional study was carried out on 100 young adults aged 15 to 29 years living in Kiriella village in Ratnapura District, Sri Lanka. Information regarding fast-food consumption level, occupation, height, weight, and other relevant facts were obtained using an online questionnaire. Both descriptive and inferential statistics were used to analyze the data. The overall fast-food consumption was 44% and 56% of males and females respectively. 17% of A/L students and 27% of university students consumed fast food at a high level. Overweight was detected among 19% of A/L students, 28% of university students, and 3% of employers. Being overweight was determined to be strongly associated with fast-food consumption. Overweight which was detected as 50% among young adults was statistically significant and highly associated with their occupation. Gender was not statistically associated with overweight. However, the study revealed that fast-food consumption among young adults is noticeably associated with overweight.